The impact of international law on international cooperation: Theoretical perspectives - Benvenisti, Eyal (Cambridge University, 2013)
Aiming to advance our understanding of the influences international norms and international institutions have over the incentives of states to cooperate on issues such as environment and trade, this book adopts two different approaches in examining this question.